Syntheses of two kinds of disaccharide subunits of antitumor antibiotic bleomycins. Issue 43 (26th October 2017) - Che, Rui; Zhu, Qiwen; Yu, Jie; Li, Jiao; Yu, Jiahui; Lu, Wei
Abstract: Gram-scale syntheses of two kinds of bleomycin disaccharides are described.l -gulose subunit12 was accomplished with a novel and short route in six steps and 37% overall yield from4, which could be easily prepared from the commercially available inexpensive materiald -sorbitol, while 6-deoxy-l -gulose subunit was synthesized in 11 steps in 8% yield fromd -glucolactone. The disaccharides were then prepared in a previously reported glycosidation coupling of the 3- O -carbamoyl-mannosyl donor with thel -gulopyranoside acceptors. Both disaccharides were finally obtained in gram-scale and the total synthesis of disaccharide2 was achieved the first time. Graphical abstract: